Burden among caregivers for children with asthma: A mixed-method study in Guangzhou, China - Miaolan Guo; Guozhen Gao; Jinlan Guo; Litao Wen; Liting Zeng (Elsevier, 2015)
Objective: Research suggests that caregivers of children with asthma experience a substantial amount of stress, though no comprehensive study examines this problem. Here we both quantitatively and qualitatively examined the burden on caregivers of children with asthma. Methods: Surveys were administered to 138 caregivers of asthmatic children by convenience sampling. The Zarit Caregiver Burden Interview (ZBI) was used to assess the degree of caregiver burden. In addition, 13 qualitative semi-structured interviews were carried out via purposive sampling and were used to explore the perception of caregivers. SPSS and content analysis were used to analyze quantitative and qualitative data, respectively. Results: We found that caregiver burden (mean = 31.56 ± 14.19) ranged from 24% with no or mild burden, 52% with mild to moderate burden, 22% with moderate to severe burden and 2% with very severe burden. Caregiver burden was also assessed as 5 different dimensions. Self-criticism ranked most burdensome (2.09 ± 1.05), followed by sacrifice (1.57 ± 0.94), embarrassment/anger (1.30 ± 0.80), dependency (1.21 ± 0.77), and lastly, loss of control (1.20 ± 0.84). The highest individually scored item on the ZBI was "fear of the future of the relative" (mean = 3.04). Interviews of caregiver burden were summarized into three main themes, namely: 1) life is too chaotic; 2) negative emotions; and 3) gaps in the medical support system. Conclusions: These findings expand our understanding about the burden caregivers of children with asthma face, and may help to propose targeted strategies to help caregivers adapt to their roles, and maintain and promote the health of themselves and their families.